Development of an eco-friendly geopolymer mortar using slag and fly ash with high bentonite content for thermal and environmental applications - Aya allah M. Ebrahim; Doaa A. Ahmed; Reham Abu-Elwafa (Scientific Reports)
Abstract The construction industry is exploring the use of low-cost waste materials to create eco-friendly geopolymer mortar binders. Our study aims to develop various environmentally friendly geopolymer mortar mixes for thermal and adsorption applications using natural materials like bentonite and industrial by-products such as ground-granulated blast furnace slag and fly ash. Ternary geopolymer mortar pastes are prepared using equimolar amounts of slag (GBFS) and fly ash (FA), with 6%, 8%, 10%, and 12% weight of bentonite (BC) from the total geopolymer weight to study the bentonite replacement effect. The prepared mortar are tested for their physico-chemical, mechanical, adsorption, and thermal stability properties (300 °C to 900 °C). The adsorption behavior of eco-friendly geopolymer mortar mixes against crystal violet dye in aqueous solutions is also identified. The study found that adding 6% bentonite to the slag/fly ash-based geopolymer mortar mix yielded the highest mechanical characteristics. Moreover, all the ternary geopolymer mortar mixes exhibited excellent thermal stability up to 900 °C. In adsorption study, the results indicated that the mortar mixes had excellent capacities and adhered well to the Freundlich isotherm model, suggesting potential applications in treating wastewater. Using bentonite in slag/fly ash geopolymer mortar offers a sustainable, cost-effective, and heat-resistant alternative to traditional cement binders.